THE INFLUENCE OF REAL INTEREST RATES, INFLATION, EXCHANGE RATE, AND GDP ON STOCK RETURN IN THE PROPERTY SECTOR - Tejokusumo, Paulin; Anastasia, Njo; Atmadja, Adwin Surja (Jurnal Ekonomi dan Manajemen, 2022)
Stocks are one of the investment products in financial markets that need to be understood in terms of risk and return, where changes in stock returns can be influenced by external and internal factors. This study aims to determine the significant effect of real interest rates, inflation, exchange rates, and gross domestic product on property sector stock returns on the Indonesia Stock Exchange (IDX) in the 2012-2019 period. This period shows a fluctuating property market cycle due to changes in external factors, namely the economy and politics in Indonesia. Public companies in the property and real estate sector are listed on the IDX, with a total of 67 companies selected with certain criteria; 26 companies were selected. Secondary data obtained from the World Bank and Bank Indonesia were tested using panel data regression. The test results show that real interest rates, inflation, and exchange rates have a significant effect on stock returns, but the gross domestic product has no significant effect. This research proves the importance of the government's role in maintaining the economic and political stability of a country so that investors are interested in investing in the stock market. Contributions from the property and real estate sector in driving the economy from upstream to downstream also need government support regarding regulations and taxation.